2013
DOI: 10.1152/ajpheart.00296.2012
|View full text |Cite
|
Sign up to set email alerts
|

Antisickling fetal hemoglobin reduces hypoxia-inducible factor-1α expression in normoxic sickle mice: microvascular implications

Abstract: Kaul DK, Fabry ME, Suzuka SM, Zhang X. Antisickling fetal hemoglobin reduces hypoxia-inducible factor-1␣ expression in normoxic sickle mice: microvascular implications. Am J Physiol Heart Circ Physiol 304: H42-H50, 2013. First published November 2, 2012; doi:10.1152/ajpheart.00296.2012.-Chronic inflammation is a salient feature of sickle cell disease (SCD) and transgenic-knockout sickle (BERK) mice. Inflammation is implicated in the activation of hypoxia-inducible factor-1␣ (HIF-1␣) under normoxic conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 59 publications
4
16
0
Order By: Relevance
“…The VE-cadherin protein concentration in lung homogenates determined by ELISA was lower in the SS NHNrf2−/− mice, consistent with the substantially elevated concentration of the adhesion molecule in the plasma of the same animals (Figure 6C). Previous studies have shown that SpO 2 in nonanesthetized transgenic SS mice is normal at steady state (31, 32), and we confirmed this finding in the SS WT(DL) mice in this study (Figure 7A). The SpO 2 in SS NHNrf2−/− mice was significantly reduced — indicative of oxygen desaturation — coupled to a low breath rate, which suggested that these mice had developed a severe respiratory disease (Figure 7, A and B).…”
Section: Resultssupporting
confidence: 91%
“…The VE-cadherin protein concentration in lung homogenates determined by ELISA was lower in the SS NHNrf2−/− mice, consistent with the substantially elevated concentration of the adhesion molecule in the plasma of the same animals (Figure 6C). Previous studies have shown that SpO 2 in nonanesthetized transgenic SS mice is normal at steady state (31, 32), and we confirmed this finding in the SS WT(DL) mice in this study (Figure 7A). The SpO 2 in SS NHNrf2−/− mice was significantly reduced — indicative of oxygen desaturation — coupled to a low breath rate, which suggested that these mice had developed a severe respiratory disease (Figure 7, A and B).…”
Section: Resultssupporting
confidence: 91%
“…We adopted this approach to monitor SS mice using a validated mouse pulse oximeter (30,31). Baseline levels of pulse oximetry oxygen saturation (SpO 2 ) were not different in SS and control mice, as reported previously (32). After challenge with 70 μmol/kg hemin, SpO 2 in SS mice decreased progressively, reaching approximately 85% for the majority within 30 minutes (Figure 2A).…”
Section: Introductionsupporting
confidence: 54%
“…21,36 Further, mitochondrial H 2 O 2 mediates the hypoxic stabilization of hypoxia-inducible factor 1a (HIF-1a), 37 which could contribute to the aberrant normoxic stabilization of HIF-1a, which has been reported in SCD and is implicated in the pathogenesis of vasculopathy. [38][39][40] Hemolysis and platelet activation are known to be closely associated in SCD patients. 14,15,29 The current study confirms this relationship and extends it to include mitochondrial dysfunction as a mechanistic link.…”
Section: Discussionmentioning
confidence: 99%